2020
DOI: 10.1152/ajpheart.00355.2019
|View full text |Cite
|
Sign up to set email alerts
|

Novel measures of left ventricular electromechanical discoordination predict clinical outcomes in children with pulmonary arterial hypertension

Abstract: Adverse ventricle-ventricle interaction and resultant left ventricular (LV) dysfunction are a recognized pathophysiological component of disease progression in pulmonary arterial hypertension (PAH) and can be associated with electrical and mechanical dyssynchrony. The purpose of this study was to investigate the clinical and mechanistic implications of LV electromechanical dyssynchrony in children with PAH by using novel systolic stretch and diastolic relaxation discoordination indexes derived noninvasively fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(67 reference statements)
1
19
0
Order By: Relevance
“…The improved strain values correlate with improvements in known prognostic markers of PAH such as 6-min walk test, pro-BNP, and mean pulmonary arterial pressure (MPAP) [ 21 ••]. Furthermore, an interventricular dyssynchronous contraction has been documented with a left-to-right delay assessed by strain in adult and paediatric patients with PAH [ 33 36 ].…”
Section: Regional Function and Strainmentioning
confidence: 99%
“…The improved strain values correlate with improvements in known prognostic markers of PAH such as 6-min walk test, pro-BNP, and mean pulmonary arterial pressure (MPAP) [ 21 ••]. Furthermore, an interventricular dyssynchronous contraction has been documented with a left-to-right delay assessed by strain in adult and paediatric patients with PAH [ 33 36 ].…”
Section: Regional Function and Strainmentioning
confidence: 99%
“…LV dysfunction is of increasing interest in pediatric PAH, since its prognostic relevance has become more apparent (20), and it may reflect LV compression as a result of RV enlargement (21). Burkett et al demonstrated the strongest correlations for maximal eccentricity index, a new and highly reproducible measure (19).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, Burkett et al demonstrated that eccentricity index and right-to-left ventricular ratio correlated with invasive simultaneous hemodynamic measurements, PH-related hospitalizations, BNP/NT-proBNP levels, and WHO FC ( 19 ). LV dysfunction is of increasing interest in pediatric PAH, since its prognostic relevance has become more apparent ( 20 ), and it may reflect LV compression as a result of RV enlargement ( 21 ). Burkett et al demonstrated the strongest correlations for maximal eccentricity index, a new and highly reproducible measure ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of an altered position of the interventricular septum, impaired LV diastolic filling (74,75) and reduced LV torsion have been reported in PH patients (76). Progressive electrical dyssynchrony occurring with RV dilatation and dysfunction further contributes to systolic LV dysfunction and a discoordinate contraction pattern that, in turn, is of prognostic relevance (31,32). Accompanied by adverse interactions on the ventricular level, increased stiffness of the ascending aorta seems to be present and is directly related to MPA distension.…”
Section: Ventricular and Vascular Right-left Heart Interactionsmentioning
confidence: 99%